C-Reactive Protein and Procalcitonin Diagnostic Value in Congenital Infection in Newborns with Extremely Low and Very Low Birth Weight - O. V. Mikhaylova; O. V. Ionov; A. G. Antonov; I. V. Nikitina; A. V. Degtyareva; A. V. Levadnaya; D. M. Nasonova; M. L. Alekseeva; T. Y. Ivanets; D. N. Degtyarev (Union of pediatricians of Russia, 2015)
The high frequency of infectious complications in the early neonatal period of adaptation in infants with extremely low (ELBW) and very low birth weight (VLBW) attracts particular attention. The aim of our study was to evaluate the sensitivity (Se) and specificity (Sp) of C-reactive protein and procalcitonin in congenital pneumonia and congenital sepsis in newborn infants with extremely low and very low birth weight.Methods. In 160 preterm newborns that were included in our prospective study, 33 had early neonatal sepsis, 42 children had congenital pneumonia, and 85 infants were without neonatal infection. A comprehensive clinical and laboratoryinstrumental examination of the newborn was done, including determining the concentration of C-reactive protein and procalcitonin at the age of 48-72 hours of life. Results. Low sensitivity of CRP at the age of 48-72 hours of life in congenital sepsis and congenital pneumonia was observed. However, under these pathological conditions CRP and PCT are characterized by high specificity. It should also be noted that PCT has a high sensitivity in children with congenital sepsis aged 48-72 hours. Moreover, PCT also has a high specificity (Sp 80,6%), which determines its advantage in the use of sepsis diagnosis in extremely premature infants compared to CRP.Conclusion. Maximum specificity reaches 100%, co-located with the assessment of CRP and PCT, which determines the feasibility of using this combination for verification of congenital infectious conditions such as sepsis and pneumonia in children ELBW and VLBW aged 48-72 hours.